The Role of Leadership in Improving Employee Work Motivation at the Secretariat of the Regional House of Representatives in West Papua Province - Ullo, Novera Yanti; Budiman, Budiman; Balia, Nikolina (Economics and Digital Business Review, 2025)
This study explores the pivotal role of leadership in bolstering employee work motivation within the Secretariat of the Regional House of Representatives in West Papua Province, addressing the need to enhance motivation as a crucial factor in improving organizational performance and service delivery. Employing a qualitative approach, the research examines the influence of different leadership styles, specifically transformational and transactional leadership, on employee motivation levels. Data were gathered through interviews with key stakeholders, including leaders and staff, supplemented by document analysis and surveys measuring employee motivation. The findings reveal that transformational leadership, characterized by vision-sharing, employee empowerment, and inspirational communication, positively impacts work motivation. Conversely, transactional leadership, with its emphasis on task completion and reward systems, provides only short-term motivation. Contextual factors such as cultural values, organizational structure, and limited professional development opportunities also play pivotal roles in shaping the effectiveness of leadership in motivating employees. The study recommends fostering a transformational leadership approach by implementing mentorship programs and increasing funding for training and development, while addressing structural and cultural barriers that hinder employee motivation. Leaders are encouraged to prioritize clear communication and recognize employee achievements to build a more motivated workforce. These insights offer valuable guidance for policymakers and organizational leaders aiming to enhance governance and operational efficiency in the public sector of West Papua Province.